The Concept of Dysphemism in French Linguistics (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article will talk about the concept of dysphemism, the feedback of linguistic scholars on this concept, the pragmatic features of dysphemisms in the French language. It has also been suggested that the phenomenon of dysphemia, its characteristic feature, dysphemia is a discursive phenomenon, and dysphemism is both a linguistic and a speech phenomenon.